'Tight' / Esmalinda Mohamad ... [et al.] - Mohamad, Esmalinda; Mohd Azlan, Siti Sarra Hazwani; Alias, Nurulain; Misri, Anis Athirah (2017)
The product is a bed sheet puller name "Tight". • The function of Tight is to tighten bed sheet with one click. • Tight is a simple technology that makes life easier, compared to normal routine of tightening the bed sheet manually at four corners every time after waking up from sleep.